The Use Of Poem In Teaching Speaking To The EleventhYear Students Of SMA N 2 Sukoharjo - WULANDARI, SHINTA; , Drs. Djoko Srijono, M. Hum (2016)
The study aim at describing the technique used by the teacher in teaching speaking using poem, the problem faced by the English teacher and students, and the way teacher and students overcomes the problems at the teaching speaking using poem at the eleventh year students of Language Department. The writer uses descriptive qualitative research. The subject of the study is the English teacher and the eleventh year students of Language Department. The method of collecting data are observation, content of document analysis, and interview. In analysing data, the writer uses an interactive model, namely, data reduction, data display, and verification of the data. Based on the research finding, the teacher used discussion in teaching speaking using poem, while the procedure on teaching speaking using poem are, 1) opening, 2) choral imitation, 3) individual imitation, 4) assignment, 5) pesentation, 6) evaluation, 7) closing. But, the teacher did not use always the same procedures. The problem face by the teacher are, 1) classroom management, 2) limited time, 3) different capability of the students. The problem face by the students are, 1) the difficulty in pronunciation the word, 2) lack of vocabulary, 3) the difficulty in spelling the word. The strategies to overcome the problems faced by the English teacher in teaching speaking using poem are, 1) the teacher gave some questions randomly to the students, 2) the teacher gave the same opportunities to the students to ask, 3) the teacher aksed students to bring the dictionary or laptop, 4) the teacher shoud give more attention to the slow learners, 5) the teacher also often gives them exercise both individually or in group. The strategies to overcome the problems faced by the students, they are: 1) the students can practice it with their friends or asks the English teacher how to pronounce the words, 2) the students also can imitate an English expression in music, film, youtube or another source, 3) they can bring dictionary or laptop in English class.